PENGARUH MOTIVASI BERPRESTASI TERHADAP KETERAMPILAN MENULIS PUISI KELAS III SDIT QURRATA AINI BAITUSSALAM - Alia Ning Tyas Apriliani; Andestend; Tika Kartika (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to determine the effect of achievement motivation on the poetry writing skills of third-grade students at SDIT Qurrata Aini Baitussalam. This study uses a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research sample consisted of 62 students divided into two groups, namely the experimental class that used visual learning media and the control class that did not use it. Data were collected through questionnaires and poetry writing skill tests (pretest and posttest). The results of the data analysis showed that there was a significant difference between the control class and the experimental class with a significance value of 0.000 < 0.05. The average posttest score of students in the experimental class was 101.6, higher than that of the control class, which was 77.7. This indicates that achievement motivation has a positive effect on students' poetry writing skills. This finding confirms that by increasing achievement motivation, students' ability to write poetry can develop significantly. Therefore, it is important for teachers to design learning that can trigger students' achievement motivation through appropriate approaches and media